2004
DOI: 10.1371/journal.pbio.0020199
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Widespread Convergent Evolution around Human Microsatellites

Abstract: Microsatellites are a major component of the human genome, and their evolution has been much studied. However, the evolution of microsatellite flanking sequences has received less attention, with reports of both high and low mutation rates and of a tendency for microsatellites to cluster. From the human genome we generated a database of many thousands of (AC)n flanking sequences within which we searched for common characteristics. Sequences flanking microsatellites of similar length show remarkable levels of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
3
25
0
2
Order By: Relevance
“…To what extent the repeat composition may have a direct or indirect influence on the low mutation rate of the adjacent exon 2 segment of the DRB7 pseudogene is not well understood at present. It has been proposed, for example, that microsatellites near genes may increase and probably also decrease local mutation rates (45). Interestingly, exon 2 of the DRB7 pseudogene, present on the only shared DR region configuration of humans and chimpanzees, is highly conserved between both species.…”
Section: Discussionmentioning
confidence: 99%
“…To what extent the repeat composition may have a direct or indirect influence on the low mutation rate of the adjacent exon 2 segment of the DRB7 pseudogene is not well understood at present. It has been proposed, for example, that microsatellites near genes may increase and probably also decrease local mutation rates (45). Interestingly, exon 2 of the DRB7 pseudogene, present on the only shared DR region configuration of humans and chimpanzees, is highly conserved between both species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that examined trinucleotide repeat lengths in primates and other species found that humans have greater repeat lengths (and greater variability between individuals-although limited variance may be the consequence of captive breeding or restricted population sampling in the other species examined) than other great apes, which in turn have longer repeat sequences than rodents. (16)(17)(18)21,22,(40)(41)(42) Thus the mechanism whereby more variability arose in this primate lineage, possibly via associated mutations regulating fidelity and proof-reading during DNA replication, could be of significance. Furthermore, the unique aspect of human evolution is that it has involved developmentally mediated expansion of specific brain regions, particularly the cerebral cortex, as well as subsequent enhancement of cognitive abilities, and therefore the relationship between TRP evolution and the genetic regulation of neurodevelopment and neural plasticity, is a question worth exploring using a combination of genomics and neuroscience approaches.…”
Section: Dynamic Mutations As Digital Genetic Modulatorsmentioning
confidence: 99%
“…Finally, we should note that we have excluded all simple repeats including AT-rich repeats from our analysis because of possible alignment artifacts. However, positions close to simple repeats exhibit an increased rate of gene conversion in the human genome (Vowles and Amos 2004), and it is thus possible that simple repeats including those in LCR22-2/LCR22-4 can potentially also undergo concerted evolution.…”
Section: Polymorphisms In Lcr22-2 and Lcr22-4mentioning
confidence: 99%